Proceedings of the 35th ACM SIGMOD-SIGACT-SIGAI Symposium on Principles of Database Systems 2016
DOI: 10.1145/2902251.2902279
|View full text |Cite
|
Sign up to set email alerts
|

Counting Answers to Existential Positive Queries

Abstract: Existential positive formulas form a fragment of first-order logic that includes and is semantically equivalent to unions of conjunctive queries, one of the most important and well-studied classes of queries in database theory. We consider the complexity of counting the number of answers to existential positive formulas on finite structures and give a trichotomy theorem on query classes, in the setting of bounded arity. This theorem generalizes and unifies several known results on the complexity of conjunctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(99 citation statements)
references
References 13 publications
2
97
0
Order By: Relevance
“…Then there is a constant k such that for all cores ψ of pp-formulas in Φ`we have twpψq ď k and twpcontractpψqq`1 ď k. With the results of Section V it follows that qawpψq ď 2k for such cores ψ. As discussed prior to the statement of Theorem 4.4, we can express, for each φ P Φ, the function |φp¨q| as a polynomial in unknowns |ψp¨q| with ψ P Φ` [18]. We can then substitute every term |ψ 1 p¨q| by a 7PP-formula of width at most 2k with the results of Section V. This yields a 7PP-formula of width at most 2k.…”
Section: Proofs Of Main Theoremsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then there is a constant k such that for all cores ψ of pp-formulas in Φ`we have twpψq ď k and twpcontractpψqq`1 ď k. With the results of Section V it follows that qawpψq ď 2k for such cores ψ. As discussed prior to the statement of Theorem 4.4, we can express, for each φ P Φ, the function |φp¨q| as a polynomial in unknowns |ψp¨q| with ψ P Φ` [18]. We can then substitute every term |ψ 1 p¨q| by a 7PP-formula of width at most 2k with the results of Section V. This yields a 7PP-formula of width at most 2k.…”
Section: Proofs Of Main Theoremsmentioning
confidence: 99%
“…Previous work showed that, for bounded arity Φ, countpΦq is fixed-parameter tractable if Φ satisfies the tractability condition; interreducible with the parameterized clique problem if Φ satisfies the contraction condition but not the tractability condition; and as hard as the parameterized counting clique problem otherwise (see [4] for a precise statement). 3 Note that in previous articles [4], [18] this graph was defined in terms of the core of the given formula.…”
Section: A Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another direction is to study the complexity of counting answers to formulas; in this problem, one is given a first-order formula and a finite structure, and the goal is to count the number of assignments, to the free variables of the formula, that satisfy the formula on the structure. There have been recent results on this direction in the context of primitive positive formulas [28,23] and existential positive formulas [24].…”
Section: Resultsmentioning
confidence: 99%